(untitled) (Ustozlar uchun, 2025)
This article analyzes the major characteristics of the metaphysical poets—John Donne, George Herbert, and Andrew Marvell. It explores their intellectual depth, complex metaphors, the blend of religious and philosophical themes, and the significance of metaphysical conceits in the evolution of English poetry.